2012
DOI: 10.1111/j.1440-1797.2012.01603.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood‐borne viruses in the haemodialysis‐dependent population attending Top End Northern Territory facilities 2000–2009

Abstract: Aim:  To describe the incidence and prevalence of blood‐borne viruses (BBV) including: hepatitis B virus (HBV), hepatitis C virus (HCV), human immunodeficiency virus (HIV) and human T‐cell leukaemia virus type‐1 (HTLV) in the haemodialysis‐dependent population of the Top End of the Northern Territory (TENT). Methods:  We retrospectively reviewed the serology of BBV in a longitudinal fashion in the haemodialysis‐dependent population treated in the TENT of Australia from 2000 to 2009 inclusive. HBV, HCV, HIV and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Overall, 15 studies were included, three cohort and twelve cross-sectional studies ( 19 - 33 ). A total of two studies were among adults(28, 31), eight among prisoners ( 19 , 20 , 22 - 24 , 29 , 32 , 33 ), three among PWID who attended NSPs ( 21 , 25 , 27 ), one among people who were haemodialysis patients ( 26 ) and one among people diagnosed with HCC ( 30 ). There was one study conducted in remote areas ( 28 ), two in regional ( 22 , 24 ), two in urban areas ( 21 , 31 ) and ten studies were national analyses or included multiple geographical locations ( 19 , 20 , 23 , 25 - 27 , 29 , 30 , 32 , 33 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, 15 studies were included, three cohort and twelve cross-sectional studies ( 19 - 33 ). A total of two studies were among adults(28, 31), eight among prisoners ( 19 , 20 , 22 - 24 , 29 , 32 , 33 ), three among PWID who attended NSPs ( 21 , 25 , 27 ), one among people who were haemodialysis patients ( 26 ) and one among people diagnosed with HCC ( 30 ). There was one study conducted in remote areas ( 28 ), two in regional ( 22 , 24 ), two in urban areas ( 21 , 31 ) and ten studies were national analyses or included multiple geographical locations ( 19 , 20 , 23 , 25 - 27 , 29 , 30 , 32 , 33 ).…”
Section: Resultsmentioning
confidence: 99%
“…These four studies did report the reasons why the participants refused to participate, including: being uncomfortable with needles and among Aboriginal people in prison; a fear that the blood test would be used to detect drug use. Seven studies had a sample size less than 400 ( 21 , 22 , 24 , 26 , 27 , 29 , 30 ), reducing the representativeness of these studies and potentially increases sampling variability when estimating the pooled prevalence of anti-HCV. There was a high degree of selection bias in nine studies as they included populations at high risk of HCV infection (Aboriginal people in prison and Aboriginal people who inject drugs) ( 19 , 20 , 22 - 25 , 29 , 32 , 33 ).…”
Section: Resultsmentioning
confidence: 99%
“…Blood borne virus infections are recognized as important hazards for patients and staff in maintenance hemodialysis (MHD) units but most studies focus on hepatitis B (HBV), hepatitis C (HCV) and human immunodeficiency virus (HIV). Few studies were specifically designed to estimate the prevalence of HTLV-1 infection in MHD patients [ 25 30 ]. These studies, conducted in the last century, revealed that, similarly to what is observed in the general population, the prevalence of HTLV-1 infection among MHD patients varies according to the geographic area.…”
Section: Introductionmentioning
confidence: 99%
“…The high prevalence of cardiovascular comorbidities, risk factors such as smoking, diabetes mellitus, and infections are among the major medical factors that affect listing on the transplant waiting list . Skin infections, dental infections and other infections associated with poor socioeconomic states such as scabies, tuberculosis and hepatitis B infections are common . These need to be assessed before listing as they negatively affect outcomes.…”
Section: High Prevalence Of Common Risk Factors Associated With Poor mentioning
confidence: 99%